Arrival architecture: migrants, urban migration, Johannesburg - Kitenge, Mutombo (My University, 2011)
This thesis is an exploration of how a predominant migrant community can help with the integration process of newly arriving migrants. As the world grows into an urban village more and more people migrate in search of a good lifestyle and economic empowerment. Different suburbs find themselves hosting a particular group of migrants, who in turn transform the community to suit their needs. a rich urban precinct is born where the migrant is central to the community facilities. The question of homing, integration and bridging between a space of home to the new community becomes more and more problematic and needs to be addressed in order to welcome migrants, and guard against issues of Xenophobia and separations between the arriving migrant and the existing community. As a result an integration facility that the migrant can arrive and learn about the community will help the community in embracing the arriving migrant and the diversity that he brings with him, so as to minimize the conception of “them” and “us”.